Cerdas dan Berkelanjutan: Bagaimana kewirausahaan digital mendorong kinerja lingkungan dan adopsi ekonomi sirkular - Dewi Puspasari; Amalia, Dinda; Djunaedi Rusli, Yus; Wisuda Purba, Daniel (LPPM Universitas Buana Perjuangan Karawang, 2026)
This study aims to analyze the development of knowledge, conceptual structures, thematic clusters, and research themes in the literature related to the Circular Economy, Innovation, and Digital Sustainability. This study uses a systematic bibliometric approach by utilizing VOSviewer and PoP software to map publication patterns, conceptual networks, and the dynamics of research development in multidisciplinary domains. Bibliographic data was obtained from the Google Scholar database, which consists of 100 reputable articles from 2018-2026 using the keywords Circular Economy Adoption, Digital Entrepreneurship, Environmental Performance, Smart and Sustainable and analyzed using keyword co-occurrence techniques, network visualization. Based on the results of bibliometric analysis of research development patterns, knowledge structures, thematic clusters, and the distribution of dominant and emerging themes, it can be concluded that the research field of Circular Economy and Digital Sustainability has experienced a significant conceptual evolution towards an integrative paradigm centered on innovation. In general, research is evolving from a traditional sustainability approach to a circular economy, and then to digital-enabled sustainability, which emphasizes the role of digital technology in supporting the transformation of a sustainable economic system